Genomics and breeding for climate-resilient crops : Vol. 2 Target Traits - Kole, Chittaranjan (Springer Berlin Heidelberg, 2013)
Climate change is expected to have a drastic impact on agronomic conditions including temperature, precipitation, soil nutrients, and the incidence of disease pests, to name a few. To face this looming threat, significant progress in developing new breeding strategies has been made over the last few decades. The second volume of Genomics and Breeding for Climate-Resilient Crops describes various genomic and breeding approaches for the genetic improvement of the major target traits. Topics covered include: flowering time; root traits; cold, heat and drought tolerance; water use efficiency; flooding and submergence tolerance; disease and insect resistance; nutrient use efficiency; nitrogen fixation; carbon sequestration; and greenhouse gas emissions.